Electrostatic influence on energetics of electron transfer reactions. - Rees, D C (1985)
Electron transfer chains in biological systems must operate efficiently to satisfy metabolic energetic requirements. The component proteins in these chains are expected to exhibit characteristic structural features that facilitate electron transfer to the appropriate donor and acceptor proteins. A survey of soluble one-electron carrier proteins indicates a significant tendency for lower potential proteins to be more negatively charged than higher potential proteins. Consideration of the electrostatic consequences of this pattern of charge asymmetry suggests that the reduction potential difference between the two proteins will be minimized in the precursor complex associated with electron transfer. An equivalent statement is that the change in free energy accompanying electron transfer in the complex will approach zero. This behavior is consistent with theoretical arguments advanced by Albery and Knowles [Albery, W. J. & Knowles, J. R. (1976) Biochemistry 15, 5631-5640], which suggest that for the most efficient enzymes, the free energy difference between enzyme-bound species should approach zero. A more general derivation of this prediction is provided. The observed charge asymmetry in electron transfer proteins provides a structural mechanism for satisfying this requirement, thus accelerating the overall rate of electron transfer.